Intertextuality and Multimodal Meanings in High School Physics: Written and Spoken Language in Computer-supported Collaborative Student Discourse. Issue 1 (2nd January 2017) - Tang, Kok-Sing; Tan, Seng-Chee
Abstract: The study in this article examines and illustrates the intertextual meanings made by a group of high school science students as they embarked on a knowledge building discourse to solve a physics problem. This study is situated in a computer-supported collaborative learning (CSCL) environment designed to support student learning through a science inquiry unit enacted in a classroom. As the CSCL environment is intensively mediated by written texts and spoken dialogue, the environment presents a unique opportunity to investigate the relationship between intertextuality and collaborative knowledge-building. Drawing from a dialogic and semiotic perspective of intertextuality, a framework based on systemic functional linguistics was used to analyse the intertextual and multimodal relations between the written and spoken forms of language used to solve the physics problem. Results indicate that in a CSCL environment, the thematic integration of the written and spoken forms of language is critical in the progress of the collaborative inquiry. In particular, written texts provide the contextual meanings to facilitate the students' collaborative discourse, while spoken language creates new meanings by building bridges across the written texts. The implications of these analyses and findings for classroom discourse as well as potential for future research are discussed.